Governmental Policies in Managing COVID-19 Pandemic: Comparative Study Between Indonesia and Vietnam, Period of January – March 2020 (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
Since WHO declared COVID-19 as a global pandemic, COVID-19 management has become a problem for countries with limited resources and weak health systems. The purpose of this article is to describe the implementation of policies in Indonesia and Vietnam, in which both countries have limited resources in facing the COVID-19 pandemic. The present study is a narrative review which compares he COVID-19 policies in two countries. The study is conducted by searching relevant literature on Google Scholar with the keywords